2014
DOI: 10.12816/0006774
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation of Spaza Shop Entrepreneurs Evidence From a Study of South African and Somali Owned Spaza Shop Entrepreneurs in Khayelitsha

Abstract: Almost twenty years after democracy we find growing economic activity in the informal sector. The spaza market in Khayelitsha 1 can be seen as an example of entrepreneurial activity offering an entry point to many that are excluded from mainstream economic activities. This study included 352 participants and is comprised of South African (locals) and Somali (foreigners) owned spaza shop entrepreneurs operating in Khayelitsha. In recent years foreigners have become a dominant force in this market often resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…It was easy because we support each other even when we do not necessarily know each other, but for the fact that we are from the same country it is easy for us to find one another". Basardien et al (2014) found that small businesses such as spaza shops run by foreign nationals are more effective than those run by natives simply because foreign nationals are said to have more business skills than South African citizens. Therefore, instead of South Africans establishing and running businesses on their own, they erect buildings in their backyards that are leased out to foreign nationals to be utilised as spaza shops.…”
Section: The Other Respondent Saidmentioning
confidence: 99%
“…It was easy because we support each other even when we do not necessarily know each other, but for the fact that we are from the same country it is easy for us to find one another". Basardien et al (2014) found that small businesses such as spaza shops run by foreign nationals are more effective than those run by natives simply because foreign nationals are said to have more business skills than South African citizens. Therefore, instead of South Africans establishing and running businesses on their own, they erect buildings in their backyards that are leased out to foreign nationals to be utilised as spaza shops.…”
Section: The Other Respondent Saidmentioning
confidence: 99%
“…It was noted that there was specific differentiation between local and foreign entrepreneurship processes Basardien et al (2014). Certain characteristics such as risk-taking by foreigners; innovative use of decommissioned containers as stores; competitiveness; and reactiveness form some of these.…”
Section: Entrepreneurial Orientation and Business Practicesmentioning
confidence: 99%
“…al. (2013), Charman et al (2012), and Basardien et al (2014) all highlight financial management as a skill which must be understood and practiced by informal businesses in order to succeed. They agree that this skill is lacking for most local Spaza shop owners.…”
Section: Financial Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…She suggested that South African business owners were largely inept and should learn from the business practices of their foreign 1 At the same time, South Africans were at a natural disadvantage because they had no history of entrepreneurfrom the moment they are born, they are introduced to trade. Their mothers, uncles, every- 2 These stereotypical comparisons are echoed in the research literature. There is a common idea in the business literature, for example, that poor black South Africans lack entrepreneurial ambition and that this helps to explain the relatively small size of the South African informal economy and the high rate of local informal business failure.…”
Section: Introductionmentioning
confidence: 97%